Changes in Food Consumption Patterns due to COVID: Is There a New Post COVID Food Consumer? - Alonso, Maria Aranzazu Sule; Rushit, Tea (New Innovations in Economics, Business and Management Vol. 9, 2022)
Food is a physiological need with an important social and cultural dimension. Eating habits have traditionally been one of the most stable factors of people's entire sociocultural heritage. However, today we are living in a time of important changes, with a great impact on the nutritional status of the population, motivated, among others, by new lifestyles and conditions, the advancement of technology and distribution systems, the emergence of new foods, new forms of preparation and processing. The main aim of this study is to investigate whether or not there has been a change in the daily dietary patterns of adults during the Coronavirus quarantine. To reach this aim, the objectives set are the following: Analyze food consumption trends, study the food consumer typologies, look at the new target post covid group of consumers, analyze the perception of distribution channels, investigate buying from groceries online and indicate the platforms for selling local food. The impact of the COVID-19 health crisis on people's food interests, opinions, and behaviour is described in this study. In addition, an online survey (Spanish population, n = 232) looked into how food buying habits changed during the pandemic. To try to cover the whole Leon territory and reach the greatest number of persons through mobile phones, tablets, and computers, the questionnaire was created using the Google Forms tool and distributed using instant messaging apps such as WhatsApp, social media such as Facebook, and Twitter, social networking sites such as LinkedIn and ResearchGate, and email through snowball sampling. The statistical analysis was carried out under the SPSS program. Using the Mediterranean Diet as a reference for healthy uptake, we may infer that the examined Spanish adult population is quite close to having good healthy dietary habits. During the confinement of COVID-19, there was an improvement in dietary behaviours.